Performance of Cucumber Cultivars at Low Hill During Summer-Rainy Seasons - Sharma, MD; Bhattarai, SP (Journal of the Institute of Agriculture and Animal Science, 2006)
This experiment was conducted in randomized block design with three replications in the farmers' field conditions at Yampaphant, Tanahun during April - July 2000. The cultivars included in this study were one commercial namely Bhaktapur Local and the four exotic cultivars and hybrids namely Malini, Korean White, Japanese Green and Green Long. The hybrid Malini was found significantly more vigor and earlier (first picking at 42 days) and produced significantly higher number of fruits (252 thousands/ha) and significantly higher yield (69.6 t/ha). The commercial variety Bhaktapur Local remained androecious and did not produce fruit when grown during summer -rainy season. Key words: Cucumber, summer-rainy season, marketable yield J. Inst. Agric. Anim. Sci. 27:169-171 (2006)